Analisis Pembelajaran Berbasis Loose Part untuk Menstimulasi Motorik Halus Anak Usia 5-6 Tahun di TK Sakti Lestari 01 Batang - Wulandari, Tiara Aulia; Khasanah, Ismatul (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2024)
This Loose part not only supports children's development, but also helps children to connect themselves with the environment. Loose part activities can be used to train fine motor skills in children. The aim of this research is to describe: 1) describe loose part-based learning in stimulating children's fine motor skills at TK Sakti Lestari 01 Batang. 02, 2) describes the obstacles and solutions to loose part-based learning in stimulating children's fine motor skills at TK Sakti Lestari 01 Batang. This type of research is descriptive qualitative research. The results of this research are: 1) TK Sakti Lestari 01 Batang is quite good at utilizing loose parts from natural materials to stimulate fine motor skills in children, 2) The obstacles that arise are related to the limited availability of loose part learning media 3) the solution provided by the school is to collaborate with children's parents in procuring loose part learning media.